THE USE OF JIGSAW TO IMPROVE SPEAKING ENGLISH ABILITY THE ELEVENTH GRADE STUDENTS OF SMA N 1 TERAS BOYOLALI IN ACADEMIC YEAR 2009/2010 - PURWANDARI, DHENI DYAH (2011)
The purpose of this study is to identify the improvement of students' speaking ability. The method used in this research is collaborative action research between the senior high school English Teacher (Teacher J) and the researcher. The research was conducted in two cycle from June1th until June 14th 2010 at the eleventh grade students of SMAN 1 Teras Boyolali. The research data are collected by using techniques of qualitative data collection which include: observation, interview, research diary and the mean score of pre-test and post-test. Photographs, audio recording, and video recording are also recorded during the implementation of the research to provide data more accurate. The data are analyzed through re-reading the research diary, pre-research observation report, and filed note. The result of the research shows that jigsaw is an effective technique to improve the students' speaking ability. The research findings include: 1) Jigsaw is able to improve the students' speaking ability especially in using grammar, using the appropriate vocabulary, and pronouncing the words correctly. Through jigsaw, students are provided with abundant opportunities to practice their ability in using the correct grammar, pronouncing the correct pronunciation and using the appropriate vocabulary. Jigsaw stimulates the students to speak; 2) The response of the students when jigsaw is applied is they tend to be more active and jigsaw attracts them in joining speaking lesson. The students can be more involved in the teaching learning process since every student has to be responsible for their own learning.